Growth and whole-body proximate composition of Oreochromis niloticus Nile tilapia fed pea meal: A systematic review and meta-analysis - Magbanua, Tzodoq Obrero; Ragaza, Janice Alano (Frontiers in Sustainable Food Systems, 2023)
One of the most widely cultivated species in the aquaculture sector is the Nile tilapia (Oreochromis niloticus). However, the rising price of fishmeal has a huge impact on its market value. Proteins derived from plants have been used to address the issue. In this study, systematic review and meta-analysis were used to quantitatively analyze the whole-body composition and growth of Nile tilapia fed pea meal. Based on the preferred reporting items for systematic reviews and meta-analysis methods, the literature review and paper selection were completed. Meta-analysis was performed on the data from peer-reviewed studies that met the inclusion screening requirements, namely: tilapia development stage, standard error reporting, feeding period, lack of nutritional supplements, and crude protein levels. The control diet outperformed the plant-based diets according to the result, in which growth and feed utilization characteristics were significantly different (P < 0.05). All except the final weight were significantly better (P < 0.05) in tilapia fed control compared to tilapia fed pea treatment. Additionally, the pooled estimate of whole-body composition of fish fed a diet based on pea meal was not substantially different from that of fish fed a diet based on fishmeal (P > 0.05). Due to large and statistically significant I2 values, the feeding interval, crude protein concentration, fish development stage, and dietary pea meal inclusions were all examined using meta-regression analysis to identify the sources of heterogeneity. Not all co-variates explained the heterogeneity except for the feeding period and crude protein % in some of the parameters. The minimum quantities of dietary pea meal needed for best Nile tilapia performance in terms of growth, feed utilization, and whole-body composition were found to be 4.9, 488.6, and 210.3 g kg−1, respectively.